Advancing Social Justice and Democracy in Teacher Education: Teacher Preparation 1.0, 2.0, and 3.0. (1st October 2016) - Zeichner, Ken
Abstract: Teacher education programs that claim the mantle of social justice often fail to practice what they preach. The three forms of teacher education introduced here outline a path to achieve a more democratic and socially just future for teacher education programs .